Opal-A in Glassy Pumice, Acid Alteration, and the 1817 Phreatomagmatic Eruption at Kawah Ijen (Java), Indonesia - Lowenstern, Jacob B.; van Hinsberg, Vincent; Berlo, Kim; Liesegang, Moritz; Iacovino, Kayla; Bindeman, Ilya N.; Wright, Heather M. (Frontiers in Earth Science, 2018)
At Kawah Ijen (Indonesia), vigorous SO2 and HCl degassing sustains a hyperacid lake (pH ~0) and intensely alters the subsurface, producing widespread residual silica and advanced argillic alteration products. In 1817, a VEI 2 phreatomagmatic eruption evacuated the lake, depositing a widespread layer of muddy ash fall, and sending lahars down river drainages. We discovered multiple types of opaline silica in juvenile low-silica dacite pumice and in particles within co-erupted laharic sediments. Most spectacular are opal-replaced phenocrysts of plagioclase and pyroxene adjacent to pristine matrix glass and melt inclusions. Opal-bearing pumice has been found at numerous sites, including where post-eruption infiltration of acid water is unlikely. Through detailed analyses of an initial sampling of 1817 eruption products, we find evidence for multiple origins of opaline materials in pumice and laharic sediments. Evidently, magma encountered acid-altered materials in the subsurface and triggered phreatomagmatic eruptions. Syn-eruptive incorporation of opal-alunite clasts, layered opal, and fragment-filled vesicles of opal and glass, all suggest magma-rock interactions in concert with vesiculation, followed by cooling within minutes. Our experiments at magmatic temperature confirm that the opaline materials would show noticeable degradation in time periods longer than a few tens of minutes. Some glassy laharic sedimentary grains are more andesitic than the main pumice type and may represent older volcanic materials that were altered beneath the lake bottom and were forcefully ejected during the 1817 eruption. A post-eruptive origin remains likely for most of the opal-replaced phenocrysts in pumice. Experiments at 25°C and 100°C reveal that when fresh pumice is bathed in Kawah Ijen hyperacid fluid for six weeks, plagioclase is replaced without altering either matrix glass or melt inclusions. Moreover, lack of evidence for high-temperature annealing of the opal suggests that post-eruption alteration of pumice is more likely than pre-eruption envelopment of euhedral opal-replaced phenocrysts in dacitic melt. At Ijen and elsewhere, the ascent of magma into hydrous acid-altered mineral assemblages (e.g., opal, kaolinite, alunite) could induce rapid dehydration of hydrous minerals and amorphous materials, generating considerable steam and contributing to magmatic-hydrothermal and phreatomagmatic explosions.